Design and Developments of an Intelligent Irrigation System - Dr. Prafull Kumar, Dr. Geeta Kandpal (International Journal of Modern Agriculture, 2021)
This paper introduces an intelligent irrigation system that is utilized in the regions that are suffering water shortage problems. Hence as an advance solution has been cons8idered to have an intelligent irrigation network system. This paper presents an intelligent irrigation system that optimizes the present water level in the water reservoir efficiently, thereby providing the irrigation techniques with even more secure and successful water usability solutions. This proposed system is capable of providing automatically services like starting and stopping of water from the pumps while functioning at the actual irrigation site depending on the present moisture content in the soil, it uses moisture content sensors along with the advance ultrasonic sensors that is used to measure the needed water levels on the irrigation site. For configuring the required control algorithms in the programs for calculating the sensor values that are sent into used Arduino microcontrollers. The system prioritizes the irrigation activities just by deciding the available number of pumps and their respective positions they are operated in any situation. Depending on their differing water needs different crops can be watered in this way. This implemented design, uses an architectural and laboratory level model was built that depicts the farm settings along with the reservoir, control units are connected with pumps running on direct current. The Experimental outcome of model have revealed many aspects from its good performance that makes this system established as an effective supplement tool required for irrigation problems.